Collaborative Practice Bidang Maternitas pada Tenaga Kesehatan - Femy Fatalina; Sunartini Sunartini; Widyandana Widyandana; Mariyono Sedyowinarso (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2015)
Background: World's current health systems are in a crisis, causing public health needs are not being met. Mother Mortality Rate in Indonesia was still high. It indicated that maternity care was not optimal yet. One of solution is an implementation of interprofessional collaborative practice. Currently, in Indonesian’s hospitals have not seen an equal team collaboration. The objective of this study was to explore the perceptions and acceptance of health workers maternity’s interprofessional collaborative practice in Dr. Sardjito Yogyakarta’s Hospital. Methods: This study was a qualitative with a phenomenology design. Subjects were nurses, midwives, obstetrics and gynecologist, pharmacists, and nutritionists who had collaboration experience in obstetrics gynecology department in Dr. Sardjito Yogyakarta’s Hospital, included 10 respondents. Sampling technique used a purposive sampling, while data collection used a Focus Group Discussion and in-depth interviews. Data’s credibility and reliability obtained by triangulation, debriefing, member checking and rich data. Research ethics included an informed consent and ethics committee’s approval. This study was conducted in February-July 2014. Result: Most respondents had a wrong perception of interprofessional collaboration’s definition. All of respondents accepted if interprofesional collaboration implemented properly. Data analysis resulted in six categories: perception of health workers about interprofessional collaboration, implementation of interprofessional collaboration in hospital, application of collaboration’s elements in interprofessional collaboration, health workers’s expectations for better collaboration, health workers’s motivation in doing interprofessional collaboration and variation of health workers’s acceptance of interprofessional collaboration. Conclusion: Most of health workers have not had a correct perception of interprofessional collaborative practice. All health workers accepted if interprofessional collaborative practice applied properly in maternity area in Dr. Sardjito Yogyakarta’s Hospital.